'Não compre, plante'? A tipificação penal das situações de cultivo de Canábis pelo Tribunal de Justiça de São Paulo - Silva, Felipe Figueiredo Gonçalves da (2016)
Brazilian Law n. 11.343 published in august of 2006 (Drug Law) creates the National System of Drug Public Policy and establishes the guidelines for the Brazilian drug policy. The Drug Law proposes an integrated approach to the drug problem grounded in two major pillars: prevention of drug use and repression of drug trafficking. Among the measures taken by the Law lies the creation of a specific criminal offence called 'growing for self-consumption' (art. 28, §1). This measure was well seen by the anti-prohibition movements and criminal scholars in general. 'Growing for personal consumption' receives the same criminal treatment as 'possession with intent to consume', with criminal sanctions composed of alternative measures to imprisonment. Art. 28 §2 of the Drug Law poses the criteria that should be used by the criminal justice system’s competent authorities to perform the criminal classification of conducts under its scope. This research is dedicated to the study of criminal classification of Cannabis crops in São Paulo’s Justice Court. The study focuses the arguments presented by the judges and their use in the decisions to justify the classification of a crop as being for personal use or with intent to sell. We seek to identify in which ways the criteria presented in Art. 28, §2 of Brazilian Drug Law are posed on the justification of the judicial rulings. One main question drives this research: what are the elements and how are they used in the criminal classification of Cannabis crops? To address the core questions the research was developed through a judicial decision research in the electronic repertoire of São Paulo’s Justice Court. The research analyses 135 decisions delivered by the court in which the grower’s intention is explicitly discussed in the context of criminal classification. The decisions studied were taken between 1998 and 2014 and were selected in accordance to the criteria stablished throughout this dissertation. The quantitative results of the empirical research are related to the general features of the procedures, evidences referred in the decisions, characteristics of the crops and justification of the criminal classification. The qualitative discussion of the research’s results is posed in four blocks: (i) interpretation and assessment of the notion of drug quantity; (ii) criminal records, circumstances of the arrest and characteristics of the agent; (iii) sale’s material and other elements relevant for criminal classification; (iv) features of the evidentiary repertoire of the criminal procedures. We expect to contribute to a better understanding of (i) the determination of intention in cases involving Cannabis cultivation and (ii) da legal consequences that stem from the legislative choice not to use threshold quantities standards for determining personal use and trafficking.